Establishing and maintaining an online community of academics: longitudinal evaluation of a virtual conference series - Thatcher, A.; Straker, Leon; Pollock, Clare (Inderscience Enterprises Ltd, 2011)
Initiated in 1996, the CybErg international conference series is the only online conference series in the field of ergonomics. Using virtual settlement theory and a model of online community evolution, this article reports on a 12-year longitudinal investigation of the five conferences in the conference series and whether they have been effective in establishing an online academic community and in internationalising the dissemination of knowledge and dialogue of this online community. The results suggest that the conference series is indeed a good example of an online community in an engaged state and has been largely successful in encouraging equality in the international distribution of contributors. This article concludes with new possibilities to enhance the conduct, knowledge production, dialogue, and processes of future online academic conferences.